Designing biomarker studies for head and neck cancer. Issue 7 (21st November 2013) - Kim, Kelly Y.; McShane, Lisa M.; Conley, Barbara A.; Myers, Jeffrey N.
Abstract Although there is ample literature reporting on the identification of molecular biomarkers for head and neck squamous cell carcinoma, none is currently recommended for routine clinical use. A major reason for this lack of progress is the difficulty in designing studies in head and neck cancer to clearly establish the clinical utility of biomarkers. Consequently, biomarker studies frequently stall at the initial discovery phase. In this article, we focus on biomarkers for use in clinical management, including selection of therapy. Using several contemporary examples, we identify some of the common deficiencies in study design that hinder success in biomarker development for this disease area, and we suggest some potential solutions. The purpose of this article is to provide guidance that can assist investigators to more efficiently move promising biomarkers in head and neck cancer from discovery to clinical practice. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1069–1075, 2014